APLIKASI PERHITUNGAN JUMLAH ZAKAT BERBASIS ANDROID - Setianingsih, Lilis; Apriyanto, Apriyanto; Abduh, Hisma (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research aims to develop applications that can relieve the public in knowing or doing zakat calculations.Where researchers directly visit the research object, BAZNAS (Badan Amil Zakat Nasional) Palopo City to obtain data and information about zakat calculation.The app uses the waterfall model as its development method. This waterfall model is a system or software development that has six levels, namely system design, analysis, design, coding, testing and maintenance. This zakat calculation application uses Android Studio.in the maker of this application uses PHP and MySQL as its data storage database and uses Black Box Testing as a testing system.With the application of zakat calculation, which can relieve the community to do zakat calculation and facilitate baznas in conveying the provisions of the price of gold and rice.